THE ROLE OF THE DEFENSE INSTITUTIONS IN HANDLING THE COVID-19 PANDEMIC - Marina Ika Sari; Yuli Ari Sulistyani; Andhini Citra Pertiwi (Indonesia Defense University, 2020)
The involvement of the military in the global health crisis has begun since the COVID-19 outbreak broke out in Indonesia, starting from the implementation of Large-Scale Social Distancing to the implementation of the new normal adaptation phase. However, the involvement has received mixed responses. Some parties consider it as natural, while others question the urgency of the military involvement. This study focuses on the role of two defense institutions, namely the Indonesian National Armed Forces and the Ministry of Defense in handling the COVID-19. It employs a qualitative research method and the theory of role, the concept of national defense, and the concept of Pandemic Management to analyze the problem. This study finds that the Indonesian National Armed Forces has a strategic role in several fields such as health, security and socio-economic as part of the efforts to contain COVID-19. The Ministry of Defense also plays a strategic role both internally and externally, by cooperating with other ministries, domestic private companies, state-owned enterprises in the defense industry sector, and with other countries in containing the COVID-19 pandemic.Keywords: role, defense, military, pandemic, COVID-19.